2005
DOI: 10.1121/1.4787004
|View full text |Cite
|
Sign up to set email alerts
|

3D spatial sampling with a cylindrical multibeam sonar array

Abstract: Various beam pair combinations can be formed with cylindrical multibeam sonar arrays to obtain a 3D spatial sampling of a patch of seafloor for each ping. This capability is explored with a 286 deg sector cylindrical array transmitting a stepped FM pulse over a 243 deg vertical fan beam centered on nadir and receiving with twenty-seven beam pairs, symmetrically steered about nadir in the fore-aft direction and spaced at 7.16 deg intervals across track. Conventional conjugate product techniques yield two across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Soc. Am., 117(4-2), 2447, 2005 Various beam pair combinations can be formed with cylindrical multibeam sonar arrays to obtain a 3D spatial sampling of a patch of seafloor for each ping. This capability is explored with a 286º sector cylindrical array transmitting a stepped FM pulse over a 243º vertical fan beam centered on nadir and receiving with twentyseven beam pairs, symmetrically steered about nadir in the fore-aft direction and spaced at 7.16º intervals across track.…”
Section: Published Abstracts Of Presentations At Meetings Of the Acoumentioning
confidence: 99%
See 2 more Smart Citations
“…Soc. Am., 117(4-2), 2447, 2005 Various beam pair combinations can be formed with cylindrical multibeam sonar arrays to obtain a 3D spatial sampling of a patch of seafloor for each ping. This capability is explored with a 286º sector cylindrical array transmitting a stepped FM pulse over a 243º vertical fan beam centered on nadir and receiving with twentyseven beam pairs, symmetrically steered about nadir in the fore-aft direction and spaced at 7.16º intervals across track.…”
Section: Published Abstracts Of Presentations At Meetings Of the Acoumentioning
confidence: 99%
“…27 fore-aft beam pairs are formed with 27 sub-arrays of 16 contiguous staves. Previous work (Brogan and de Moustier, 2005;2006) has shown that time and angles of arrival of seafloor echoes received at the VSS array can be used to obtain swath bathymetry and seafloor acoustic backscatter imagery. This report is a preliminary analysis of the uncertainties in estimation of the angles of arrival of bottom echoes received by pairs of VSS beams.…”
Section: Technical Reportsmentioning
confidence: 99%
See 1 more Smart Citation